2013
DOI: 10.1177/0956462413487321
|View full text |Cite
|
Sign up to set email alerts
|

Use of tablet-based kiosks in the emergency department to guide patient HIV self-testing with a point-of-care oral fluid test

Abstract: Objective Despite successes in efforts to integrate HIV testing into routine care in emergency departments, challenges remain. Kiosk-facilitated, directed HIV self-testing offers one novel approach to address logistical challenges. Methods Emergency department patients, 18–64 years, were recruited to evaluate use of tablet-based-kiosks to guide patients to conduct their own point-of-care HIV tests followed by standard-of-care HIV tests by healthcare workers. Both tests were OraQuick Advance tests. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 9 publications
3
65
1
Order By: Relevance
“…In an urban sexually transmitted disease clinic, 80% of eligible patients accepted HIV testing and 87% of those accepted POC HIV tests [131]. Patients will even accept to perform their own HIV test in Emergency Departments with some being recruited via kiosks [107,108,110]. …”
Section: New Hiv Poc Testsmentioning
confidence: 99%
“…In an urban sexually transmitted disease clinic, 80% of eligible patients accepted HIV testing and 87% of those accepted POC HIV tests [131]. Patients will even accept to perform their own HIV test in Emergency Departments with some being recruited via kiosks [107,108,110]. …”
Section: New Hiv Poc Testsmentioning
confidence: 99%
“…A study of adult emergency room patients in Baltimore, MD, USA showed that: 96.1% agreed to a self-point-of-care HIV test; 100% had concordant results with those of a trained provider; 91.7% “trusted the results very much”; and 98.4% reported performing the test was “easy” 33. An emergency department study that offered oral fluid self-tests and directions on tablet-based kiosks found that 49.5% accepted testing, and 100% of results were concordant between users and trained providers 34. Another study in Baltimore offered oral or finger stick self-testing to emergency room patients undergoing point-of-care oral fluid testing by a health care professional and showed that: 85% of participants consented to self-testing; 91% chose oral fluid over finger stick; 99.6% of self-test results agreed with health care professionals’ results; and 84.4% of testers trusted their result 35.…”
Section: Arguments For Hiv Self-testing: Accessibility; Accuracy; Empmentioning
confidence: 99%
“…15 Haukoos et al . evaluated the use of triage-based kiosks to obtain consent for HIV screening in an ED.…”
Section: Introductionmentioning
confidence: 99%